Spray Drying of Blueberry Juice-Maltodextrin Mixtures: Evaluation of Processing Conditions on Content of Resveratrol - César Leyva-Porras; María Zenaida Saavedra-Leos; Elsa Cervantes-González; Patricia Aguirre-Bañuelos; Macrina B. Silva-Cázarez; Claudia Álvarez-Salas (MDPI AG, 2019)
Resveratrol is an antioxidant abundant in red fruits, and one of the most powerful inhibiting reactive oxygen species (ROS) and oxidative stress (OS) produced by human metabolism. The effect of the spray drying processing conditions of blueberry juice (BJ) and maltodextrin (MX) mixtures was studied on content and retention of resveratrol. Quantitatively, analysis of variance (ANOVA) showed that concentration of MX was the main variable influencing content of resveratrol. Response surface plots (RSP) confirmed the application limits of maltodextrins based on their molecular weight, where low molecular weight MXs showed a better performance as carrying agents. After qualitatively comparing results for resveratrol against those reported for a larger antioxidant molecule (quercetin 3-D-galactoside), it was observed a higher influence of the number of active sites available for the chemical interactions, instead of stearic hindrance effects.